Application of Order as Character Education in Santriwati Islamic Boarding School Jagad Alimussiry - Zubaidah, Eny (http://jagadalimussirry.com/, 2020)
Every institution has its own way or method of applying character education where the lessons of values, ethics, morals and religious teachings are the main focus. The boarding school has a different educational pattern than the one in general. At the Alimussirry World Boarding School, students have a set of rules that are used in practice in the daily schedule of students. The daily schedule of activities was a means of implementing the practice for the students under the supervision of the lodge managers. All activities have different areas of management to assist and supervise studentsCharacter education is not just about the young budding education process that is tapping into the formation of the school, it is also about the individual within the educational institution. Basically, in order to be a responsible individual in society, each individual must develop a wide range of potentials within himself, especially promoting morals that will serve as a guide for their role models within the institution.